Water Recovery from Brine Solution by Forward Osmosis Process (Journal of Engineering, 2013)
The present work aims to study the possibility of utilization a forward osmosis desalination process as an alternative method to extract water from brine solution rejected from reverse osmosis process. Experiments conducted in a laboratory–scale forward osmosis (FO) unit in cross flow flat sheet membrane cell yielded water flux ranging from (0.0315 to 0.56 L/m2 .min) when using CTA membrane,and ranging from (0.419 to 2.785 L/m2 .min) for PA membrane under 0.4 bar. Two possible membrane orientations were tested. Sodium chloride with high concentrations was used as draw solution solute. The effect of membrane orientation on internal concentration polarization (ICP) was studied. Two regimes of ICP; dilutive and concentrative were described and characterized and their governing equations were applied. Also the effect of draw and feed solution concentrations and flow rate were studied. It was found that the experimental water flux were lower than the theoretical water flux. Using of PA membrane under pressure was resulted in a higher flux of desalinated water than when CTA used alone without pressure under the same operating conditions.